Asymmetric Biomechanical Properties of the Paravertebral Muscle in Elderly Patients With Unilateral Chronic Low Back Pain: A Preliminary Study - Wu, Zugui; Ye, Xiangling; Ye, Zixuan; Hong, Kunhao; Chen, Zehua; Wang, Yi; Li, Congcong; Li, Junyi; Huang, Jinyou; Zhu, Yue; Lu, Yanyan; Liu, Wengang; et al. (Frontiers in Bioengineering and Biotechnology, 2022)
Background: Clinical incidences of chronic low back pain among the elderly are increasing. However, studies have not fully elucidated on changes in biomechanical properties of paravertebral muscles in patients with unilateral chronic low back pain. We evaluated the changes in biomechanical properties of painful and non-painful paravertebral muscles in elderly patients with unilateral chronic low back pain. Methods: Biomechanical properties of paravertebral muscles, including muscle tone and stiffness, in elderly patients with unilateral chronic low back pain were measured using MyotonPRO. Lumbar Lordosis and Sacral Slope were measured by magnetic resonance imaging. Cross-sectional areas of paravertebral muscles were evaluated using Image J software version 1.53. Chronic low back pain severity was assessed by Visual Analogue Scale (VAS) and Oswestry Disability Index (ODI) scores. The correlations between VAS scores, ODI scores, Lumbar Lordosis, Sacral Slope, cross-sectional areas (painful side), disease duration, and biomechanical properties of paravertebral muscles in the painful side were analyzed. Results: A total of 60 elderly patients with unilateral chronic low back pain were enrolled in this study. The muscle tone and stiffness of paravertebral muscles on the painful side were significantly higher than those on the non-painful side (p < 0.05). Cross-sectional areas of paravertebral muscles on the painful side at the L3 level were smaller than those of the non-painful side (p<0.05). The VAS scores and ODI scores were significantly positively correlated with muscle tone and stiffness of paravertebral muscles on the painful side (p < 0.05 and p < 0.01, respectively). There were no significant correlations between disease duration, cross-sectional areas (painful side), Lumbar Lordosis, or Sacral Slope and muscle tone and stiffness of paravertebral muscles on the painful side (p > 0.05). Conclusions: In elderly patients with unilateral chronic low back pain, muscle tone and stiffness of paravertebral muscles on the painful side are higher than for those on the non-painful side. The asymmetry of biomechanical properties of paravertebral muscles is associated with severity of chronic low back pain.